'A Saint if ever there was One': Henry Robert Reynolds (1825–96). (4th January 2016) - Binfield, Clyde
Abstract : A 'saint if ever there was one, but who might have been a little more effective had there been in his nature some slight traces of the old Adam'. Thus William Hardy Harwood (1856—1924) reflecting on a past member of Sub Rosa, a long-established essay club for Congregational ministers in Greater London. Harwood could only have known this particular saint for four years and perhaps his recollection is best seen as a businesslike minister's snapshot of an other-worldliness outside the normal run of Nonconformist experience. It betrays a degree of affectionate irritation. It is almost a dismissal. Free Churchmen don't do saints.